Transapical aortic valve implantation - What have we learnt? Quo vadis? - Beller, Carsten J. (Cardiovascular Diagnosis and Therapy, 2012)
After Alain Cribier pioneered in 2002 the transfemoral approach to transcutaneous aortic valve implantation (TAVI) (1), the Leipzig Heart Center was the first to perform a transapical TAVI in December 2004.